The Effect of Using Technology in Learning on Student Learning Motivation: Analysis of the Effectiveness of Inclusive Education Programs - Latumeten, Victoria D. V.; A. Fitriani; Permatasari, Armita; Juniati, Sri Rahayu; Wahyuniar (International Journal of Educational Research Excellence (IJERE), 2024)
The objective of this study is to assess the efficacy of technology in inclusive education on enhancing student learning outcomes. The research methodology employed is a comprehensive literature review, encompassing data from various sources pertaining to the integration of technology in educational settings. The findings indicate that the incorporation of technology in inclusive classrooms can markedly enhance student learning outcomes, particularly in developing cognitive and critical thinking abilities. Additionally, technology can facilitate the optimization of the learning process in terms of efficiency and effectiveness. It is also important to note that the use of technology in education presents certain challenges and risks that must be managed effectively in order to achieve optimal outcomes. Therefore, when considering the use of technology in education, it is essential to carefully select and integrate technology in a manner that is conducive to achieving desired results.